Technology enhanced innovative assessment : development, modeling, and scoring from an interdisciplinary perspective - Jiao, Hong; Lissitz, Robert W. (MARCES book series., 2017)
Assessment innovation tied to technology is greatly needed in a wide variety of assessment applications. This book adopts an interdisciplinary perspective to learn from advances in developing technology enhanced innovative assessments from multiple fields. The book chapters address the development of virtual assessments including game-based assessment, simulation-based assessment, and narrative based assessment as well as how simulation and game based assessments serve both formative and summative purposes. Further, chapters address the critical challenge of integrating assessment directly into the learning process so that teacher effectiveness and student learning can be enhanced. Two chapters specifically address the psychometric challenges related to innovative items. One chapter talks about evaluating the psychometric properties of innovative items while the other chapter presents a new psychometric model for calibrating innovative items embedded in multiple contexts. In addition, validity issues are addressed related to technology enhanced innovative assessment.It is hoped that the book provides readers with rich and useful information about the development of several types of virtual assessments from multiple perspectives. The authors include experts from industry where innovative items have been used for many years and experts from research institutes and universities who have done pioneering work related to developing innovative items with formative applications to facilitate learning. In addition, expert advice has been provided on validating such work.